Cambios Tomográficos en la densidad ósea de alveolos post exodoncia de terceros molares inferiores doce meses después de intervenidos con plasma rico en fibrina versus cicatrización fisiológica (2021)
Objectives: The objective of this work is to determine the changes in density, height and thickness of the bone cortex in post-extraction alveoli of lower third molars at 12 months undergoing Platelet Rich Fibrin.